Deleterious somatic variants in 473 consecutive individuals with ovarian cancer: results of the observational AGO-TR1 study (NCT02222883) - Hauke, Jan; Hahnen, Eric; Schneider, Stephanie; Reuss, Alexander; Richters, Lisa; Kommoss, Stefan; Heimbach, André; Marmé, Frederik; Schmidt, Sandra; Prieske, Katharina; Gevensleben, Heidrun; Burges, Alexander; et al. (Journal of medical genetics, 2019)
Background For individuals with ovarian cancer (OC), therapy options mainly depend on BRCA1/2 germline status. What is the prevalence of deleterious somatic variants, that is, does genetic tumour testing identify subgroups of individuals who also might benefit from targeted therapy? - Methods Paired analysis of tumour-derived versus blood-derived DNA to determine the prevalence of deleterious somatic variants in OC predisposition genes (ATM, BRCA1/2, BRIP1, MSH2/6, PALB2, RAD51C/D and TP53) and the PIK3CA and PTEN genes in individuals with OC (AGO-TR1 study, NCT02222883). Results were complemented by BRCA1, PALB2 and RAD51C promoter methylation analyses and stratified by histological subtype; 473 individuals were included. - Results The combined analyses revealed that deleterious germline variants in established OC predisposition genes (all: 125/473, 26.4%; BRCA1/2: 97/473, 20.5%), deleterious somatic variants in established OC predisposition genes excluding TP53 (all: 39/473, 8.2%; BRCA1/2: 30/473, 6.3%) and promoter methylation (all: 67/473, 14.2%; BRCA1: 57/473, 12.1%; RAD51C: 10/473, 2.1%; PALB2: 0/473) were mutually exclusive, with a few exceptions. The same holds true for deleterious somatic PIK3CA and/or PTEN variants (33/473, 7.0%) found to be enriched in endometrioid and clear cell OC (16/35, 45.7%); 84.3 % of the deleterious single-nucleotide/indel germline variants in established OC predisposition genes showed significantly higher variant fractions (VFs) in the tumour-derived versus blood-derived DNA, indicating a loss of the wild-type alleles. - Conclusion Tumour sequencing of the BRCA1, BRCA2, PIK3CA and PTEN genes along with BRCA1 and RAD51C promoter methylation analyses identified large subgroups of germline mutation-negative individuals who may be addressed in interventional studies using PARP or PI3K/AKT/mTOR inhibitors. - Trial registration number NCT02222883